Chemical separation of disc components using RAVE - Wojno, Jennifer; Boeche, Corrado; Just, Andreas; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2016)
We present evidence from the RAdial Velocity Experiment (RAVE) survey of chemically separated, kinematically distinct disc components in the solar neighbourhood. We apply probabilistic chemical selection criteria to separate our sample into α-low (‘thin disc’) and α-high (‘thick disc’) sequences. Using newly derived distances, which will be utilized in the upcoming RAVE DR5, we explore the kinematic trends as a function of metallicity for each of the disc components. For our α-low disc, we find a negative trend in the mean rotational velocity (Vϕ) as a function of iron abundance ([Fe/H]). We measure a positive gradient ∂Vϕ/∂[Fe/H] for the α-high disc, consistent with results from high-resolution surveys. We also find differences between the α-low and α-high discs in all three components of velocity dispersion. We discuss the implications of an α-low, metal-rich population originating from the inner Galaxy, where the orbits of these stars have been significantly altered by radial mixing mechanisms in order to bring them into the solar neighbourhood. The probabilistic separation we propose can be extended to other data sets for which the accuracy in [α/Fe] is not sufficient to disentangle the chemical disc components a priori. For such data sets which will also have significant overlap with Gaia DR1, we can therefore make full use of the improved parallax and proper motion data as it becomes available to investigate kinematic trends in these chemical disc components.
Gesehen am 06.11.2017